The Fall of Global Socialism A Counter-Narrative From the South - Jayatilleka, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
This radical new perspective from the Global South casts a fresh light on a major aspect of contemporary history and in doing so suggests an alternative interpretation of twentieth century revolutions, Socialism, left thinking and radical politics.
Keywords: International relations; Terrorism; Political violence; World politics; Russia—Politics and government; Political theory; Political science; International Relations; Terrorism and Political Violence; Political History; Russian and Post-Soviet Politics; Political Theory; Political Science